Evaluation of Cytotoxic Effects of Different Concentrations of Porous Hollow Au Nanoparticles (PHAuNPs) on Cells. (19th January 2014) - Rao, Smitha; Huang, Chienwen; Tata, Uday; Wu, Peter; Arora, Nikhil; Ahn, Jinsung; Lin, Victor K.; Hao, Yaowu; Chiao, J.-C.
Abstract : Nanoparticles (NPs) have been introduced as a suitable alternative in many in vivo bioapplications. The risks of utilizing nanoparticles continue to be an ongoing research. Furthermore, the various chemicals used in their synthesis influence the cytotoxic effects of nanoparticles. We have investigated the cytotoxicity of Porous Hollow Au Nanoparticles (PHAuNPs) on cancer cell lines PC-3, PC-3ML, and MDA-MB-231 and the normal cell line PNT1A. Cell proliferation for the different cells in the presence of different concentrations of the PHAuNPs was assessed after 24 hours and 72 hours of incubation using MTT assay. The study also included the cytotoxic evaluation of pegylated PHAuNPs. Identical cell seeding densities, particle concentrations, and incubation times were employed for these two types of Au nanoparticles. Our results indicated that (1) impact on cell proliferation was concentration dependent and was different for the different cell types without cellular necrosis and (b) cellular proliferation might be impacted more based on the cell line.